Opinião pública e opinião publicada: representação política, Diretas Já e a grande imprensa nos (des)caminhos da abertura - Muniz, Maria Luiza de Castro (2010)
This work was dedicated to the study of editorials published during the campaign Diretas Já, by two newspapers of the mainstream media: the Folha de S. Paulo and O Globo. By the emphasis on published opinion I tried to demonstrate aspects of the class vision printed by the newspapers analyzed and by the sector of the bourgeoisie which they represent. This analysis, made with themes previously defined, consisted of the approach to ―horizon of expectations‖ outlined by the mainstream press in the opening period, transition, and especially during the succession process in 1984. I tried to enhance dissonant prospects, as a counterpoint, which eventually showed preferences for certain editorial interpretation of the recent past, the present and future projected in the pages of the newspapers. Understanding the political and ideological position of the bourgeois and liberal press demanded to study the assimilation of liberal ideology in Brazil and its conservative commitments that were part of this process. To provide a broader perspective of the opinions printed, national and international conjunctures were analyzed together, and it was highlighted the influence of the latter on the political and economic direction of Brazil. Since there was the 'deviation' represented by the mobilization around the Diretas Já, selected newspapers differed regarding the limits and scope of popular participation. But considering the convergence between the newspapers, prevailed the defense of class interests preserved by the mainstream press, bourgeois and liberal. This seeks to legitimize itself in the new situation as democratic spokesman for the national expectations, determining valid ways and exceeded invalid ways